ANTIOXIDANT CAPACITY OF FRANGIPANI (Plumeria alba) POWDER EXTRACT - Wrasiati, Luh Putu; Wirawan, I Gede Putu; Agus Bagiada, Nyoman; Mantik Astawa, I Nyoman (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES, 2012)
This research aimed to identify the antioxidant capacity, vitamin C (ascorbic acid), and total phenolic compounds of frangipani flower powder. The powder was extracted using ethanol, methanol, acetic acid, and water (aquadest). Antioxidant capacity of each extract were determined using 2,2-diphenyl-1-picrylhydrazyl radical scavenging method, vitamin C were determined using 2,4 Dinitrophenylhydrazine, and total phenolic compounds were determined using Folin Ciocalteu reagent. All of parameters were measured by spectrofotometer. The result shows that the highest value of antioxidant capacity was ethanolic extract (18.19%) and the lowest value was acetic acid extract (12.74%). The highest value of vitamin C was aqueous extract (3.49 mg/100g) and the lowest value was acetic acid extract (3.02 mg/100g). The highest value of total phenolic content was aqueous extract (25.49 mg GAE/g) and the lowest value was acetic acid extract (22.74 mg GAE/g). In conclusion, the higher antioxidant capacity was not always followed by the higher of vitamin C and total phenolic compounds.
Keywords: antioxidant capacity, vitamin C, phenolic compounds, extract of frangipani powder